Synthesis and optical properties of atomically thin transition metal dichalcogenides - Lu, Xin (2017)
Interest in two dimensional (2D) layered transition metal dichalcogenides (TMDs) has been rejuvenated within the past decade, particularly in the mono- and few-layers. The fascinating properties, such as valley polarization and strong photoluminescence (PL), have attracted more and more researches into 2D materials. In this thesis, I will introduce my work on the synthesis and optical properties of mono- and few-layer TMD materials, mainly taking MoSe2 as an example. Both top-down (mechanical exfoliation and thermal annealing thinning) and bottom-up methods will be presented. As the growth inside a chemical vapor deposition (CVD) chamber has been proven to be successful and efficient for the preparation of atomically thin TMD samples, CVD-synthesis of MoSe2 and WSe2 thin films and nanoflakes will be demonstrated. Optical properties on the as-grown samples will be shown, with PL, Raman, and optical absorption spectra displayed. The investigation on optical properties will focus on phonon properties. Firstly, relationship on stacking sequences and the evolutional trend of interlayer shear modes in MoSe2 with increasing thickness will be demonstrated. Subsequently, electrical control of phonon properties in MoS2 will be shown. Dependence on excitation energy of Vtg-related Raman shift will be discussed in detail as well.